Pemaknaan Seragam Seksi Bagi Operator Perempuan SPBU 54.801.50 Denpasar - Lamopia, I Wayan Gede; Wulandari, Riza (Asketik: Jurnal Agama dan Perubahan Sosial, 2017)
This study aims to describe the meaning of sexy uniforms for female GAS STATION operators. The phenomenon is there, operational standards and grooming at the GAS STATION 54.801.50 Denpasar, incompatible with the generally happens. The existence of rules for wearing sexy lingerie for women operators became one of the requirements for workers. This research uses qualitative research methods with types of case studies. The phenomenology of theories about the construction of self dissects the motives of the purposes and motives because the property of Alfred Schutz was chosen to analyze this research. The results of this study showed a dar motive cause and motive purpose for the operators of the woman who wears sexy uniforms at the time of work. There are three things the motive cause that is educational, economic, and social conditions. While there are purpose motives pda self-identity and comfort in doing the job obtained in addition to fulfilling the rules of the company.